2020
DOI: 10.1016/j.pce.2020.102884
|View full text |Cite
|
Sign up to set email alerts
|

Measuring soil evaporation from a cropped land in the semi-arid Makanya catchment, Northern Tanzania: Methods and challenges

Abstract: Estimating soil water loss from cropped land is vital for sustainable management of water resources in semi-arid and hot regions. Soil evaporation (Es) is an important process in these regions but hard to quantify. The study aimed at quantifying Es in maize field under three treatments using microlysimeters (MLs). It also aims to identify sources of challenges in the method. The treatments were; flat cultivation with mulching (FCM), without mulches (FC) and double digging (DD, manual tillage practice), were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Cabangon and Tuong [38] used straw mulch to cover soil cracks, which not only helped to retain moisture in the soil, but also limited the development of cracks. Nyabwisho et al [39] applied three different types of treatments in a semi-arid area of Northern Tanzania in East Africa to determine the amount of soil evaluation; among which, one is mulching. They used micro lysimeters to quantify soil evaporation and found that with mulching, soil evaporation is reduced by 28%.…”
Section: Introductionmentioning
confidence: 99%
“…Cabangon and Tuong [38] used straw mulch to cover soil cracks, which not only helped to retain moisture in the soil, but also limited the development of cracks. Nyabwisho et al [39] applied three different types of treatments in a semi-arid area of Northern Tanzania in East Africa to determine the amount of soil evaluation; among which, one is mulching. They used micro lysimeters to quantify soil evaporation and found that with mulching, soil evaporation is reduced by 28%.…”
Section: Introductionmentioning
confidence: 99%
“…Williams et al (2004) illustrated that 95% of precipitation that reaches dryland ecosystems is lost through evapotranspiration and transpiration accounts for about 64% of total evapotranspiration globally (Good et al, 2015). Evapotranspiration is usually studied by using methods such as lysimeter measurements, the Bowen ratio, and eddy covariance approaches (Cassiani et al, 2015;Kucera et al, 2017;Jin et al, 2018;Nyabwisho et al, 2020). All of these methods can provide important information about ecosystem responses to environmental variability, but none of these approaches can be used to accurately evaluate the water consumption of individual plants.…”
Section: Introductionmentioning
confidence: 99%